A novel approach to designing air filters: Ubiquitous material-based Janus air filter modules with hydrophilic and hydrophobic parts - Park, Sol; Koo, Hye Young; Yu, Chengzhong; Choi, Won San (ELSEVIER SCIENCE SA, 2021)
A ubiquitous material (sponge or cotton fabric)-based Janus air filter (JAF) with an optimized ratio of hydrophilic (75%) and hydrophobic (25%) parts was prepared using a simple and economical process that did not require specialized equipment or multiple steps. As a result of the hydrophobic part of the JAF, the adsorption of particulate matter (PM) was higher at the rear than at the front of the hydrophilic part of the JAF. The amount of PM adsorbed was further increased in the hydrophilic part of the JAF when the degree of hydrophobicity was increased in the hydrophobic part. The sponge/cotton JAFs exhibited excellent recyclability of up to 30 cycles with consistent long-term performance (RE: 99.99% and Delta P: 61 Pa) at extremely high PM2.5 concentrations (over 624,230 mu g/m(3)) and air velocities (1.05 m/s). A modular JAF could achieve the performance of 99.89% at a PM0.3 concentration of 999 mu g/m(3) and air velocity of 1.05 m/s with a low pressure drop of 152 Pa.